APPLICATION OF ARTIFICIAL INTELLIGENCE IN MEDICAL EDUCATION AND MEDICAL DIAGNOSTICS - Valitov, Elyor (University Research Base, 2024)
The field of artificial intelligence (AI) is a recent addition to technology. Its goal is to simulate, extend, and expand human intellect via the study and development of theory, method, technique, and application system using computer technology. New artificial intelligence technologies have brought about significant changes to the traditional medical setting. For instance, a patient's diagnosis derived from biochemical, endoscopic, ultrasonographic, radiographic, and pathological exams has been successfully advanced with reduced human workload and increased accuracy. Better surgical outcomes have significantly improved the medical care provided during the perioperative phase, which includes preoperative planning, surgery, and postoperative recuperation. AI technology has also significantly influenced the development of medicinal drugs and changed the course of medical administration, teaching, and research. This review's objectives are to outline the use of AI in medicine and offer a forecast for the next developments.